Evaluation of Conventional Pap Test for Cervical Intraepithelial lesions and Cancer in a Tertiary Hospital of Bangladesh - Nasreen, Mehnaz; Ahamad, M Shahab Uddin; Bhattacharjee, Pradip; Hassan, Md Quamrul; Rahman, Md Zillur (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Objective: This study was aimed to evaluate the conventional Papanicolaou (Pap) test for detection of cervical intraepithelial lesions and cancer, with histopathologic association, in a tertiary hospital of a developing country. Methods: A crosssectional hospital-based study was carried out in a total of 550 women, who underwent Pap smear examination, followed by colposcopy. Specimen adequacy and reporting was assessed according to the revised Bethesda system. 195 of these women, either Pap test positive, colposcopically positive or both, subsequently had their cervical tissue examination done with routine histopathology, as histopathology is the gold standard and Pap smear test was compared with it. Results: Among the total of 195 positive cases, histologic diagnosis of 104 (53.33%) cases were negative for cervical intraepithelial lesions or cancer, 64 (32.82%) were cervical neoplasia grade I (CIN I), 19 (9.74%) showed features of cervical intraepithelial neoplasia grade 2 and 3 (CIN II and III) and 08 (04.11%) as squamous cell carcinoma. The sensitivity and specificity of Pap test were 89.01% and 91.31%, respectively. Positive predictive value was 91.01%, while the negative predictive value was 90.56%. Conclusion: The findings of this study will be utile in supporting some useful information of Pap test, which plays a potential role in detection of cervical cancer and its precursors in a developing country like Bangladesh, where HPV-DNA test or liquid-based cytology is too expensive. DOI: http://dx.doi.org/10.11566/cmoshmcj.v12i2.31 Chatt Maa Shi Hosp Med Coll J 2013; 12(2): 1-6